Etching-Induced Surface Reconstruction of NiMoO4 for Oxygen Evolution Reaction - Zhu, Jinli; Qian, Jinmei; Peng, Xuebing; Xia, Baori; Gao, Daqiang (Nano-Micro Letters, 2023)
Rational reconstruction of oxygen evolution reaction (OER) pre-catalysts and performance index of OER catalysts are crucial but still challenging for universal water electrolysis. Herein, we develop a double-cation etching strategy to tailor the electronic structure of NiMoO4, where the prepared NiMoO4 nanorods etched by H2O2 reconstruct their surface with abundant cation deficiencies and lattice distortion. Calculation results reveal that the double cation deficiencies can make the upshift of d-band center for Ni atoms and the active sites with better oxygen adsorption capacity. As a result, the optimized sample (NMO-30M) possesses an overpotential of 260 mV at 10 mA cm−2 and excellent long-term durability of 162 h. Importantly, in situ Raman test reveals the rapid formation of high-oxidation-state transition metal hydroxide species, which can further help to improve the catalytic activity of NiMoO4 in OER. This work highlights the influence of surface remodification and shed some light on activating catalysts. Highlights: 1 Double-cation etching induces abundant vacancies serving as active sites and accelerates the surface reconstruction. 2 NMO-30M with cation deficiencies and oxygen vacancies exhibits outstanding OER performance and remarkable stability. 3 In situ Raman spectroscopy directly captures the surface reconstruction process.